Identification of a novel KCNQ1 mutation associated with both Jervell and Lange-Nielsen and Romano-Ward forms of long QT syndrome in a Chinese family - Liu Jing; Yang Junguo; Cheng Lingling; Zhang Shirong; Wang Pengyun; Ren Xiang; Yin Ke; Zhang Su; Liu Mugen; Wang Qing (BMC, 2008)
Abstract Background Long QT syndrome (LQTS) is a cardiac disorder characterized by prolonged QT intervals on electrocardiograms (ECG), ventricular arrhythmias, and sudden death. Clinically, two inherited forms of LQTS have been defined: autosomal dominant LQTS or Romano-Ward syndrome (RWS) not associated with deafness and autosomal recessive LQTS or Jervell and Lange-Nielsen syndrome (JLNS) associated with deafness. Methods A Chinese family with both RWS and JLNS was identified. Family members were diagnosed based on the presence of a prolonged QT interval as seen on a 12-lead ECG and a medical history of syncope, palpitation, and deafness. Mutational studies in the KCNQ1 potassium channel gene were performed using direct DNA sequence analysis and restriction length polymorphism analysis. Results The proband in the Chinese family and her brother had previously been diagnosed with JLNS, and two other members were affected with RWS. The proband was also affected with atrial fibrillation. A single nucleotide substitution of C to T at nucleotide 965 of KCNQ1 was identified, and the mutation resulted in the substitution of a threonine residue at codon 322 by a methionine residue (T322M). The novel heterozygous T322M mutation was identified in two patients with RWS, one member with borderline QTc, and two normal family members. The two JLNS patients in the family carried the homozygous T322M mutation. The T322M mutation was not found in 200 Chinese normal controls. Conclusion Our results suggest that T322M is a novel mutation that caused RWS with high intrafamilial variability in the heterozygous carriers and typical JLNS in the homozygous carriers within this Chinese family. The T322M mutation is the first mutation identified for JLNS in the Chinese population.